Colourimetric Estimation of Escitalopram Oxalate in Formulation by Ion Association Complex with Methyl Orange - Hemalatha, Pushparaj; Ganesh, Mani; Mei Peng, Mei; Tae Jang, Hyun (Asian Journal of Chemistry, 2013)
A new and fully validated ion pair spectrophotometric method has been developed for estimation for escitalopram oxalate in bulk and tablet formulation using acidic methyl orange dye as an ion associating agent in the absence of buffer. The developed method is sensitive and specific for the intended purpose of estimation. Ion association complex of escitalopram oxalate and methyl orange obeys Beer's law in the range of 4-24 μg mL-1 of escitalopram oxalate with a correlation coefficient of 0.9987. Accuracy, precision, stability, LOD, LOQ, interference, robustness and ruggedness were studied for validation of the method. The results recovery with low % RSD of 0.88-1.02; precision is also good in agreement with validation limits. The method developed was successfully applied for the estimation of the escitalopram oxalate in its formulation.